Online journalism education in Rwanda: students find value in the Experiential Learning Approach - Joseph Njuguna; Margaret Jjuuko (University of Johannesburg, 2019)
The digital age is reshaping media industries locally and globally, forcing media firms and media producers to master new media tools in order to remain competitive and employable. This technological revolution has had a marked impact on the structures and economic viability of media, necessitating media training institutions to rethink how they prepare future media professionals for work in the twenty-first century. In order to keep pace with these rapid technological changes, educational institutions have had to adjust journalism curricula to integrate online or multimedia journalism courses that build online competencies and the technological skills needed for graduates to flourish in digital media domains. Despite these efforts, industry players still decry the apparent unpreparedness of graduates, largely attributing this to the learning approach taken by universities. Quality skills training has been argued to ensure that learners can relate with real work life. However, in countries like Rwanda, little is known about whether these new strategies are fostering the knowledge, skills and professional dispositions needed to work in a country that is undergoing rapid technological and economic change. Drawing from experiential learning theory, this study uses five focus-group discussions from five Rwandan journalism schools to glean the views of final-year students on how trainers employ practical pedagogy to cultivate students' online skills in readiness for employment. Findings reveal that students consider the experiential learning approaches to be essential to their perceived online readiness. These enhanced skills were achieved using digital scenarios relating to students' future work environment. However, the perceived quality of this experience varied from trainer to trainer, based on a range of factors including their how students perceived the trainers' attitudes towards new media, their perceived ability to teach the digital skills and the learners' own digital experience and competence. How to cite this article: NJUGUNA, Joseph; JJUUKO, Margaret. Online journalism education in Rwanda: students find value in the Experiential Learning Approach. Scholarship of Teaching and Learning in the South. v. 3, n. 2, p. 84-101, Sept. 2019. Available at: https://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=91&path%5B%5D=48 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/